Analisis Implementasi Continuous Auditing pada Inspektorat Kabupaten Gorontalo - Alya Nurlail Mudeng; Rio Monoarfa; Usman (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This digitalization progress affects the accounting process which also has an impact on the audit process. New technologies that help lighten the audit work are starting to emerge, one of which is continuous auditing which has the concept of real-time audit testing without disrupting the company's operational processes and reducing the time lag between the initial report and the audit result report. The achievement of the APIP capability of the Gorontalo Regency area has reached level 3, meaning that it is able to manage risks and is able to provide early warnings. However, in reality there is a phenomenon of corruption cases in Gorontalo Regency with a not insignificant number. Therefore, this study aims to determine how Continuous Auditing is implemented at the Gorontalo Regency Inspectorate. This research method uses a qualitative method with a descriptive approach. There are 2 informants in this study. In this study, data was collected using observation, interview, and documentation techniques. The results of this study indicate that the Gorontalo Regency Inspectorate has implemented Continuous Auditing in village financial management, namely in the form of Siswaskeudes (Village Financial Supervision System).